Pro jQuery 2.0 - Freeman, Adam (Apress Imprint: Apress, 2013)
jQuery 2.0 is the latest version of the jQuery framework. Suitable for modern web browsers it provides a robust API for web application development. It is fast becoming the tool of choice for web developers the world over and sets the standard for simplicity,flexibility and extensibility in website design. In Pro jQuery 2.0 seasoned author, Adam Freeman, demonstrates how to get the most from jQuery 2.0 by focussing on the practical features of the technology and how they can be applied to solving real-world problems. In this comprehensive reference he goes in depth to give you the practical knowledge that you need. Each topic is covered clearly and concisely, and is packed with the details you'll need to learn to be truly effective. The most important features are given a no-nonsense, in-depth treatment, and chapters contain examples that demonstrate both the power and the subtlety of jQuery.